HUBUNGAN POPULASI CACING TANAH TERHADAP C-ORGANIK DAN N-TOTAL DI LAHAN BUDIDAYA HORTIKULTURA DAN MONOKLUTUR TANAMAN KOPI DI DESA NDUARIA KECAMATAN KELIMUTU - Muksin Muksin; Agustinus J.P Anasaga (Agriculture Faculty of Flores University, 2021)
This study aims to determine the relationship between Earthworm Population and C-organic and N-total in Horticulture and Coffee Monoculture cultivation in Nduaria Village, Kelimutu District. This research was conducted using an exploratory method that is carried out by direct observation from the observation location. How to calculate earthworms using the hand sorting method. The method commonly used for the determination of C-organic is the Walkley and Black method, while the method used for the determination of N-total is the Kjehdahl method. This method is used because it is considered simple, fast, easy to do, and requires little equipment. The results of this study indicate that in horticultural land there is no earthworm population found at all depths. Earthworm populations were found at all depths in the coffee plantation monoculture, the highest population was at a depth of 0-10 cm as many as 41 m2, Biomass was 9 g, and Biomass vs Population 0.21 m2. In horticultural fields, the highest c-organic and n-total is at a depth of 0-10 cm, the c-organic value is 3.03% (high criteria) and n-total is 0.47% (medium criteria). The close relationship between the earthworm population, biomass, and biomass versus population was positively correlated with c-organic and n-total in horticultural land and coffee monoculture.